2017
DOI: 10.1590/1807-1929/agriambi.v21n12p872-877
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics and physical and chemical characterization of white-fleshed ‘pitaya’ peels

Abstract: A B S T R A C TThe objective of this work was to obtain the drying kinetic curves of white-fleshed 'pitaya' peels and characterize the obtained powder regarding physical and chemical parameters. Different mathematical models were fitted to the experimental data of drying kinetics, considering the coefficient of determination (R²), mean square deviation (MSD) and residual distribution as fit criteria. The peels had an initial moisture content of 93.38% (w.b.) and final moisture contents of 5.39% at temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
(10 reference statements)
3
26
0
3
Order By: Relevance
“…It is evident the effect of temperature on 'bacaba' pulp dehydration, where lower moisture content in the sample was observed at the highest temperature and shortest time interval, related to the increase of the energy of water molecules, which allowed greater diffusion from the structure of the material (Sousa et al, 2018). These results are consistent with the behavior observed in the drying of fruits such as pear (Doymaz, 2013), pitaya (Santos et al, 2017) and lemon (Wang et al, 2018).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…It is evident the effect of temperature on 'bacaba' pulp dehydration, where lower moisture content in the sample was observed at the highest temperature and shortest time interval, related to the increase of the energy of water molecules, which allowed greater diffusion from the structure of the material (Sousa et al, 2018). These results are consistent with the behavior observed in the drying of fruits such as pear (Doymaz, 2013), pitaya (Santos et al, 2017) and lemon (Wang et al, 2018).…”
Section: Resultssupporting
confidence: 81%
“…According to Santos et al (2017), the mathematical model can only be used to predict drying results if the residuals are random; otherwise it will be inadequate. Doymaz (2013) and Goneli et al (2014) selected, by fitting different equations to the drying data of pear slices and aroeira leaves, respectively, the Midilli model to describe the dehydration, while Santos et al (2017) reported that the Page model was the one which best represented pitaya pulp drying. These results corroborate those of the present study, as they demonstrate the proper application of these models in the description of the drying process of agricultural products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter n of the Page model and parameter k of the models increased as the drying air temperature increased. This is because parameter k represents the effect of external drying conditions and the parameter n infers about the effect of internal drying conditions (dos Santos, de Figueirêdo, Queiroz, & Santos, 2017; Simpson, Ramírez, Nuñez, Jaques, & Almonacid, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The disposal of industrial wastewater into water bodies, without proper treatment, can cause severe damage to the environment and human health (Mostafa, 2015;Santos et al, 2017). Textile industries are present in most countries due to a human need for clothing and varied utility uses.…”
Section: Introductionmentioning
confidence: 99%